The Role of Libraries in Increasing Students' Interest in Reading - Moh. Hosnan Arisandi; Evi Lailatus Sa'adah; Anis Sofiya Rahayu (Penerbit Hellow Pustaka, 2024)
This research examines the role of the Tanamera 1 Elementary School library as a literacy and learning center through analysis of interviews with library managers and class teachers as well as questionnaires to 13 students in class V. The results show a high level of student satisfaction (92%) with library services, indicating success in creating an environment that supports interest in reading and learning. Libraries play an important role in supporting the school curriculum and developing students' information literacy skills. The circulation service received a perfect rating, reflecting good service quality. However, there are areas that require improvement, especially in terms of facility comfort. This research also reveals the potential for future library development, including modernizing collections and improving facilities. In conclusion, the SDN Tanamera 1 library has succeeded in meeting students' information needs and creating a strong literacy culture, but there is still room for further innovation and improvement.